Capital prices and Eurozone competitiveness differentials - Philippe Askenazy (Institute for the Study of Labor (IZA), 2013)
Competitiveness differentials are blamed for the instability of the Eurozone. Most of the analyses focus on labour costs or labour-market institutions. This paper explores an additional source of differentials in competitiveness: land and building prices. European countries, especially France, have experienced a significant rise in property prices since the beginning of the century. Germany is an exception. A large increase in the prices of buildings, structures and lands for private companies can be also observed in some countries. Higher prices impede firm competitiveness in at least two ways: a) investments are more costly; b) the increasing value of non-financial assets should translate into higher equity value and thus incite firms to increase dividends so as to preserve firm owners' direct remuneration. French national accounts provide rich information for exploring these mechanisms. We show that the nominal value of buildings, structures and land owned by non-financial corporations dramatically increased relative to their value added, well above their historical observations. We argue that, in France, non-financial corporations (NFCs) pay a large supplementary cost for their investments and have to distribute massive additional dividends. The yearly charge counts for at least 4% of their value added.
Keywords: E22; E31; J30; 330; Eurozone; competitiveness; non-financial asset prices; housing bubble